Adverse complications of frozen elephant trunk, do we have enough quality data?. Issue 11 (7th September 2022) - Howard, Callum; Al‐Tawil, Mohammed; Geragotellis, Alexander; Abdelhaliem, Amr
Abstract: Background: Frozen elephant trunk has in recent times become a mainstay for total arch replacement in aortovascular surgery and is indicated to treat a spectrum of complex aortic pathologies. However, despite associated excellent postoperative results it is incredibly important to recognize potential adverse complications such as negative aortic remodeling, endoleak, and distal stent‐graft induced new entry so that outcomes can be further improved. Aim of the study: Below we provide commentary on a recent article in the Journal of Cardiac Surgery discussing the topic. Conclusions: Despite the fascinating outcomes of this systematic review and meta‐analysis the heterogeneity of the literature regarding these adverse outcomes remains an issue which can only be solved with large multicenter trials directly comparing graft types as well as indications for surgery.